Scavenger receptor B2 is a cellular receptor for enterovirus 71 - Yamayoshi, Seiya; Yamashita, Yasuko; Li, Jifen; Hanagata, Nobutaka; Minowa, Takashi; Takemura, Taro; Koike, Satoshi (Nature medicine, 2009)
Enterovirus 71 (EV71) causes hand, foot and mouth disease, a mild infectious disease that can, however, occasionally lead to severe neurological impairments. These two studies, by Nishimura et al . and Yamayoshi et al ., independently identify two different receptors for EV71—P-selectin glycoprotein ligand-1 ((PSGL-1) and scavenger receptor class B, member 2 (SCARB2) ( pages 728–729 ) and ( pages 794–797 ). Enterovirus 71 (EV71) belongs to human enterovirus species A of the genus Enterovirus within the family Picornaviridae 1 . EV71, together with coxsackievirus A16 (CVA16), are most frequently associated with hand, foot and mouth disease (HFMD) 1 . Although HFMD is considered a mild exanthematous infection, infections involving EV71, but not CVA16, can progress to severe neurological disease, including fatal encephalitis, aseptic meningitis and acute flaccid paralysis 2 . In recent years, epidemic and sporadic outbreaks of neurovirulent EV71 infections have been reported in Taiwan, Malaysia, Singapore, Japan and China 3 , 4 , 5 , 6 , 7 . Here, we show that human scavenger receptor class B, member 2 (SCARB2, also known as lysosomal integral membrane protein II or CD36b like-2) is a receptor for EV71. EV71 binds soluble SCARB2 or cells expressing SCARB2, and the binding is inhibited by an antibody to SCARB2. Expression of human SCARB2 enables normally unsusceptible cell lines to support EV71 propagation and develop cytopathic effects. EV71 infection is hampered by the antibody to SCARB2 and soluble SCARB2. SCARB2 also supports the infection of the milder pathogen CVA16. The identification of SCARB2 as an EV71 and CVA16 receptor contributes to a better understanding of the pathogenicity of these viruses.